Giant field dependence of the low temperature relaxation of the magnetization in a dysprosium(III)-DOTA complex - Car, Pierre-Emmanuel; Perfetti, Mauro; Mannini, Matteo; Favre, Annaick; Caneschi, Andrea; Sessoli, Roberta (Chemical communications (Cambridge, England), 2011)
The square antiprismatic Na[Dy(DOTA)(H(2)O)]·4H(2)O complex was characterised by single crystal X-ray diffraction and ac magnetic susceptometry. Two competing mechanisms for magnetic relaxation as well as the remarkable increase of six orders of magnitude in the relaxation time upon application of a static magnetic field were detected.